CFD modelling of particle shrinkage in a fluidized bed for biomass fast pyrolysis with quadrature method of moment - Liu, Bo; Papadikis, Konstantinos; Gu, Sai; Fidalgo, Beatriz; Longhurst, Philip J.; Li, Zhongyuan; Kolios, Athanasios (Elsevier, 2017)
An Eulerian-Eulerian multi-phase CFD model was set up to simulate a lab-scale fluidized bed reactor for the fast pyrolysis of biomass. Biomass particles and the bed material (sand) were considered to be particulate phases and modelled using the kinetic theory of granular flow. A global, multi-stage chemical kinetic mechanism was integrated into the main framework of the CFD model and employed to account for the process of biomass devolatilization. A 3-parameter shrinkage model was used to describe the variation in particle size due to biomass decomposition. This particle shrinkage model was then used in combination with a quadrature method of moment (QMOM) to solve the particle population balance equation (PBE). The evolution of biomass particle size in the fluidized bed was obtained for several different patterns of particle shrinkage, which were represented by different values of shrinkage factors. In addition, pore formation inside the biomass particle was simulated for these shrinkage patterns, and thus, the density variation of biomass particles is taken into account.
Keywords: Fluidized bed; Biomass; Fast pyrolysis; CFD; QMOM; Particle shrinkage